2014
DOI: 10.1111/jvim.12330
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Potential Therapeutic Targets in Canine Thyroid Carcinoma

Abstract: BackgroundThyroid carcinoma is a common endocrine tumor in the dog. Local invasive growth frequently precludes surgical excision and, in up to 38% of dogs, the tumor has already metastasized by the time of diagnosis. Therefore, it is important to investigate new treatment modalities that may be useful for the large number of dogs with inoperable tumors or metastatic disease.Hypothesis/ObjectivesTo investigate the immunohistochemical expression of potential therapeutic targets in canine thyroid tumors.Animals74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 23 publications
1
51
3
3
Order By: Relevance
“…This staining pattern have been described in canine tumors of different origin (Hifumi et al 2010, Kim et al 2012, Teng et al 2012, Campos et al 2014 including lymphomas (Bergman et al 1996, Ginn 1996, Lee et al 1996. However, in our study, except typical cytoplasmic reaction, a dot-like staining pattern was found.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This staining pattern have been described in canine tumors of different origin (Hifumi et al 2010, Kim et al 2012, Teng et al 2012, Campos et al 2014 including lymphomas (Bergman et al 1996, Ginn 1996, Lee et al 1996. However, in our study, except typical cytoplasmic reaction, a dot-like staining pattern was found.…”
Section: Discussioncontrasting
confidence: 54%
“…However, the P-gp is highly conserved across species and the monoclonal antibody clone C494 used in our study is known to cross-react with canine tissues (Ginn 1996). This antibody has been frequently used during the last two decades in studies on P-gp expression in dogs in normal tissues (Ginn 1996), pathological conditions ( Van der Heyden et al 2011) and in various types of tumors (Ginn 1996, Lee et al 1996, Hifumi et al 2010, Campos et al 2014). Clone C219 is another most widely used monoclonal antibody for P-gp detection in canine tissues (Bergman et al 1996, Lee et al 1996, Uozurmi et al 2005, Van der Heyden et al 2011, Kim et al 2012, Teng et al 2012, Flood-Knapik et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a better understanding of the molecular mechanisms and intracellular networks associated with oncogenesis may help discover new therapeutic options for these malignancies (Malaguarnera et al, 2012). Alterations in the expression of growth factors such as insulin-like growth factor (IGF)-1, vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF)-2, and their receptors, play a role in the progression of thyroid cancer in humans and dogs (de Araujo-Filho et al, 2009;Redler et al, 2013;Campos et al, 2014). The activation of the IGF system is associated with the pathogenesis of a variety of human neoplasias because of the mitogenic and anti-apoptotic properties of its cognate receptor (Vella et al, 2001;Ciampolillo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%